Closed Financial Loops: When They Happen in Government, They're Called Corruption; in Medicine, They're Just a Footnote - De Jesus-Morales, Kevin (The Hastings Center report, 2017)
Many physicians are involved in relationships that create tension between a physician's duty to work in her patients’ best interest at all times and her financial arrangement with a third party, most often a pharmaceutical manufacturer, whose primary goal is maximizing sales or profit. Despite the prevalence of this threat, in the United States and globally, the most common reaction to conflicts of interest in medicine is timid acceptance. There are few calls for conflicts of interest to be banned, and, to our knowledge, no one calls for conflicted practitioners to be reprimanded. Contrast our attitudes in medicine with public attitudes toward financial conflicts among government employees. When enforcement of rules against conflict of interest slackens in the public sector, news organizations investigate and publish their criticism. Yet even when doctors are quoted in the media promoting specific drugs, their personal financial ties to the drug maker are rarely mentioned. Policies for governmental employees are strict, condemnation is strong, and criminal statutes exist (allowing for corruption charges). Yet the evidence that conflict is problematic is, if anything, stronger in medicine than in the public sector. Policies against conflicts of interest in medicine should be at least as strong as those already existing in the public sector.